Investigating Temporal Control in Photoinduced Atom Transfer Radical Polymerization - Dadashi-Silab, Sajjad; Lee, In Hwan; Anastasaki, Athina; Lorandi, Francesca; Narupai, Benjaporn; Dolinski, Neil D.; Allegrezza, Michael L.; Fantin, Marco; Konkolewicz, Dominik; Hawker, Craig J.; Matyjaszewski, Krzysztof (Macromolecules, 2020)
External regulation of controlled polymerizations allows for controlling the kinetics of the polymerization and gaining spatial or temporal control over polymer growth. In photoinduced atom transfer radical polymerization (ATRP), light irradiation (re)generates the copper catalyst to switch the polymerization on. However, removing the light does not immediately inactivate the catalyst, nor does the rate of polymerization become zero as chains may grow in the dark because of continued activation by the residual activator catalyst or regeneration of the Cu catalyst in the dark. In this paper, the effect of polymerization components on photoinduced ATRP was investigated to understand the interplay of temporal control and light switching. Kinetics of polymerization were monitored using in situ NMR as well as under conventional batch conditions. The extent of the polymerization in the dark depended on the activity of the Cu catalyst, which was regulated by the nature of the ligand and reaction medium. For highly active catalysts, the equilibrium concentration of the L/CuI activator is very low, and it was rapidly depleted by radical termination reactions, yielding temporal control which closely matched the switching of light to on or off. Decreasing the activity of the Cu catalyst increased the equilibrium concentration of the activator, leading to significant chain growth in the dark.
Keywords: Controlled polymerization; Equilibrium concentration; External regulations; Light irradiations; Photoinduced ATRP; Radical termination reactions; Rate of polymerization; Temporal controls